PEMBERDAYAAN DAN ADVOKASI HUKUM BAGI PEKERJA MIGRAN INDONESIA DI BRUNEI DARUSSALAM: MENINGKATKAN KESADARAN HAK DAN PERLINDUNGAN HUKUM SERTA ADAPTASI SOSIAL: Legal Empowerment and Advocacy for Indonesian Migrant Work-ers in Brunei Darussalam: Enhancing Rights Awareness, Legal Pro-tection, and Social Adaptation - Fakultas Hukum Universitas Negeri Surabaya; Dita Perwitasari; Arinto Nugroho; Vita Mahardhika; Hananto Widodo; Mahendra Wardhana (Fakultas Hukum, Universitas Negeri Surabaya, 2025)
This article examines a community service program focusing on legal empowerment and advocacy for Indonesian Migrant Workers (IMWs) in Brunei Darussalam. IMWs often experience legal vulnerability due to limited awareness of labor rights, migration regulations, and access to legal assistance, as well as challenges in social adaptation within the host country. The program was implemented through legal education sessions, participatory discussions, and advocacy assistance involving migrant worker communities. The results indicate a significant improvement in legal awareness, understanding of rights and obligations, and social adaptation skills among participants. From a legal perspective, community-based legal empowerment serves as a strategic approach to strengthening protection mechanisms, preventing labor disputes, and enhancing the overall well-being of Indonesian migrant workers abroad.